1995
DOI: 10.1021/jm00017a007
|View full text |Cite
|
Sign up to set email alerts
|

Cardioselective Anti-Ischemic ATP-Sensitive Potassium Channel Openers. 3. Structure-Activity Studies on Benzopyranyl Cyanoguanidines; Modification of the Cyanoguanidine Portion

Abstract: Structure-activity relationships for the cyanoguanidine portion of the lead cardiac selective ATP-sensitive potassium channel (KATP) opener (3) are described. The cyanoguanidine moity appears to be optimal since increasing or decreasing the distance between the aniline nitrogen and the pendant aromatic ring attenuates anti-ischemic potency/selectivity. Similarly, unfavorable results are obtained by replacement of the aniline nitrogen with other linkers (CH2, S, O). Replacement of the phenyl ring with a methyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 9 publications
(32 reference statements)
2
37
0
Order By: Relevance
“…Reactions of amines with 4-nitrophenyl chloroformate lead to carbamate 4-nitrophenylesters. 3,22 These substances are stable under standard conditions and easy to separate. Further reaction with another amine gives disparately substituted ureas.…”
Section: -[mentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions of amines with 4-nitrophenyl chloroformate lead to carbamate 4-nitrophenylesters. 3,22 These substances are stable under standard conditions and easy to separate. Further reaction with another amine gives disparately substituted ureas.…”
Section: -[mentioning
confidence: 99%
“…with halogen) are found quite often. 3,4 Until now, there is no example where these structures are used for the preparation of no-carrier-added (n.c.a.) fluorine-18 labelled analogue or original tracers for diagnostics with positron-emission-tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
“…(3)) was the first cardioselective KCO [42]. Starting from BMS-180448 Atwal et al [43][44][45][46][47] performed detailed SAR studies (Fig. 4).…”
Section: Cardioselective Benzopyranyl Cyanoguanidinesmentioning
confidence: 99%
“…Modifications of the cyanoguanidine portion [44] show that a phenyl cyanoguanidine or phenyl urea moiety strongly favor cardioselectivity; modifying the distance between aniline nitrogen and the pendant aromatic ring attenuates potency and selectivity. Replacements of the aniline N by O, S, or CH 2 are detrimental as well.…”
Section: Urinary Incontinencementioning
confidence: 99%
“…Similarly, interacting the intermediate 4-nitrophenyl carbonate ester with the adjacent amino function (4) leads to the formation of oxazolidin-2-one derivatives (5). [2][3][4][5] Using the same approach, Izdebski et al 6 reported a convenient method for the preparation of symmetrical and unsymmetrical 1,3-disubstituted ureas (9) by treating amines (6) with 1 to give 4-nitrophenyl N-alkylcarbamates (7), followed by reacting the mixture with the second amines (8). This strategy was later utilized to prepare biologically active compounds including: 1) pyridyl urea analogues as cardioselective anti-ischemic ATP-sensitive potassium channel openers; 2) N-(ureidoalkyl)-benzyl-piperidines as potent CC chemokine receptor-3 (CCR-3) antagonists;…”
Section: Introductionmentioning
confidence: 99%